Determinação da energia de fratura em materiais cerâmicos em altas temperaturas - Santos, Sérgio Francisco dos (2005)
In this work, the main objective was to determine the energy of fracture in ceramic materials, focused on refractories, at high temperatures and to inquire the interference of the creep on this measurement. Therefore, castable containing white fused and calcined aluminas, hydrated alumina as a binder, with and without, a glass of SiO2-CaO-Al2O3-B2O3-MgO was designed. This material can simulate the real situation of refractory castables that present possible glassy phase formation due to the presence of cement, silica fume and impurities of raw materials. In addition to this material two commercial refractories were also characterized. Physical characterizations, refractoriness under load, modulus of rupture, Young's modulus and coefficient of linear thermal expansion were evaluated. The energy of fracture was measured through stable crack propagation in three-point bending tests. The creep curves were obtained in three-point bending and compression tests. The concept of rate of energy of creep deformation was used to evaluate creep semiquantitatively as well as to consider a description for the energy of fracture at high temperatures. The results indicate that a maximum in the energy of fracture measured through stable crack propagation under three-point bending tests occurs as a function of temperature. For this case it will exist a range of temperature at which the material will suffer a transition from brittle to ductile behaviour due to the presence of glassy phase in the microstructure. In the transition, bridges of glassy phase contribute for the increase of the average energy for crack propagation. Consequently, these results have strong influence on the thermal shock damage resistance parameters.